2012
DOI: 10.3390/v4102097
|View full text |Cite
|
Sign up to set email alerts
|

Serological Assays Based on Recombinant Viral Proteins for the Diagnosis of Arenavirus Hemorrhagic Fevers

Abstract: The family Arenaviridae, genus Arenavirus, consists of two phylogenetically independent groups: Old World (OW) and New World (NW) complexes. The Lassa and Lujo viruses in the OW complex and the Guanarito, Junin, Machupo, Sabia, and Chapare viruses in the NW complex cause viral hemorrhagic fever (VHF) in humans, leading to serious public health concerns. These viruses are also considered potential bioterrorism agents. Therefore, it is of great importance to detect these pathogens rapidly and specifically in ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 104 publications
(153 reference statements)
0
23
0
1
Order By: Relevance
“…No existen pruebas comerciales para arenavirus, solo los grupos de investigación especializados y grandes laboratorios de salud pública poseen pruebas de ELISA o IFI. Existe una importante reactividad cruzada entre los diferentes tipos de virus, por lo que el diagnóstico específico solo puede realizarse por medio de anticuerpos neutralizantes, los cuales aparecen entre 12 a 30 días del inicio de los síntomas y durante la convalecencia (6,32,33,34).…”
Section: Aseptic Meningitis and Encephalitis By Arenavirus Of Lymphocunclassified
See 2 more Smart Citations
“…No existen pruebas comerciales para arenavirus, solo los grupos de investigación especializados y grandes laboratorios de salud pública poseen pruebas de ELISA o IFI. Existe una importante reactividad cruzada entre los diferentes tipos de virus, por lo que el diagnóstico específico solo puede realizarse por medio de anticuerpos neutralizantes, los cuales aparecen entre 12 a 30 días del inicio de los síntomas y durante la convalecencia (6,32,33,34).…”
Section: Aseptic Meningitis and Encephalitis By Arenavirus Of Lymphocunclassified
“…This technique implies direct contact with the virus, which is highly infecting, and therefore it must be carried out only in labs with category 4 biosecurity. During some years, specific RNA-PCR for arenavirus have been created which may be used in category three labs (6,32,33).…”
Section: Arenavirus En Suraméricamentioning
confidence: 99%
See 1 more Smart Citation
“…Also, replicationcompetent VSV hybrid viruses can be generated that accommodate the envelope gene from various heterologous viruses and incorporate these envelopes into the VSV particle [14][15][16][17][18][19][20][21]. The cellular tropism of the VSV hybrid virus is now dictated by the new envelope, and neutralizing antibodies against the pathogenic virus neutralize the hybrid virus [22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 98%
“…While the detection of a new positive IgG titer combined with an IgM response in the correct clinical setting may support a diagnosis of Lassa fever, the detection of a positive IgG response alone is insufficient to make a diagnosis. Lassa IgG titers may persist for decades (64), and seroprevalence studies in regions of endemicity have shown 4 to 55% of healthy individuals living in areas where the virus is endemic have detectable Lassa virus IgG titers (14,52,55,65,66).…”
Section: Antigen and Antibody Detection Assaysmentioning
confidence: 99%